Effective Communication in Negotiations - Stoikov, Lyubomir (Research Papers, 2014)
In the paper the nature and characteristics of effective communication during negotiations are examined. Thesis argues that successful negotiations are mostly a result of effective business communication, ability of the negotiators to communicate persuasively, fairly, clearly and understandable. Special emphasis is placed onnegotiation cycle, vocabulary of negotiations, difficulties and the most common barriers, effective tactics and techniques for obtaining advantage, as well as relevant aspects of verbal and nonverbal communication in negotiations.Quality exchange of information during business discussions, ability for quick orientation in the opportunities, attitudes and intentions of the negotiating parties, and the ability to encode and read signals and messages transmitted in this process - all this shows how important is good communication in the situation of negotiations.Finally, the paper notes that negotiations are kind of business communication in which the main objective is to overcome differences, reach an agreement and a deal. Summary is displayed and the success of the negotiations depends to a large extent by application of appropriate tactics, by concentrating on the details of the negotiation and the use of techniques to achieve good intermediate results as a step towards the intended general goal.